Teaching Quality Improvement on the Wards: How We Do It - Elliot Tapper; Amy Sullivan; Anjala Tess (Association of American Medical Colleges, 2015)
Abstract The Accreditation Council for Graduate Medical Education announced in 2012 that the next round of accreditation standards, the Clinical Learning Environment Review (CLER) program, would seek to "generate national data on program and institutional attributes that have a salutary effect on quality and safety in settings where residents learn and on the quality of care rendered after graduation." The CLER program's ultimate goal is to encourage the graduate medical education learning environment to deliver both high-quality physicians and safer, higher quality patient care. Graduate medical education programs are being asked to formally teach their trainees quality improvement (QI) and patient safety by engaging them in their institutional QI work. We believe that the key to engaging trainees in this work is to immerse them in solving the problems they see every day in their environment. We have developed a modular QI curriculum with the goals of framing clinical problems in a QI context, efficiently teaching house staff about a specific clinical topic while enhancing knowledge of QI methodology, allowing house staff to contribute to the improvement of a relevant clinical process, and achieving CLER goals in the context of a specific clinical rotation. The approach we detail can be adapted to any clinical environment. We implemented our quality improvement (QI) curriculum as a longitudinal program that spanned multiple rotations of house staff as a lunchtime talk format. Each successive group of rotating house staff builds on the progress of the last. The goal of the curriculum was to increase practical knowledge regarding QI intervention implementation. While this can be applied in any setting, we deployed this among medicine house staff rotating on a liver service. Our target audience is any teaching service (medicine or otherwise). The effectiveness of our program is measured in two ways. First, the program was able to produce tangible, implemented QI interventions that continue to impact care. Second, all participants completed a pre− and postsurvey that is used to assess engagement in ACGME CLER goals and obtainment of medical knowledge. Our review of the survey results demonstrates significant increases in engagement and knowledge.